EKSISTENSI TRADISI PENGANTIN SAHUR DALAM SUKU BANJAR DESA PULAU PALAS KABUPATEN INDRAGIRI HILIR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : Indragiri Hilir Regency has the distribution of the banjar tribe from the island of Kalimantan and natural geographical conditions that have similarities with the banjar tribe on the island of Borneo. One example of a tradition for the banjar tribe that has been going on for quite a long time in Riau is the tradition of "Bride of Sahur" which aims to awaken the community In the village of Palas Island, Tembilahan Hulu District, Riau Regency, they have a very unique tradition that cannot be found in other Riau areas. The purposes of this writing are as follows: (1) To determine the background of the birth of the tradition of the sahur bride in Palas Island Village, Indragiri Hilir Regency (2) To find out the process of the tradition of the sahur bride in Palas Island Village, Indragiri Hilir Regency (3) To find out the community's efforts to remain maintaining and preserving the tradition of the bride and groom sahur in Palas Island village is still carried out every year. In this study the authors used a qualitative method with data coagulation techniques including: (1) Observation, (2) Interview, (3) Documentation, (4) Literature, (5) Data analysis. Starting from the activities of the community, usually the ones that wake the community Sahur village, this sahur bride is divided into 3 procedures that take place. and also this sahur bride has given a wide influence in the recognition of Palas Island village to people from outside the region and the process of the event has been getting more festive since it has become a cultural festival but which is done by juxtaposing a bridal couple whose woman is replaced by a man and dressed just like a bride generally. The first time it was implemented in 1981 which was pioneered by several young people from Palas Island village, it has provided a diversity of traditions in the Riau Province.Keywords: Existence, Tradition, Sahur Bride, Banjar Tribe